Fetal Oxygen and Glucose Consumption in Human Pregnancy Complicated by Fetal Growth Restriction. Issue 3 (March 2020) - Cetin, Irene; Taricco, Emanuela; Mandò, Chiara; Radaelli, Tatjana; Boito, Simona; Nuzzo, Anna Maria; Giussani, Dino A.
Abstract : In healthy pregnancy, glucose and oxygen availability are essential for fetal growth and well being. However, how substrate delivery and fetal uptake are affected in human pregnancy complicated by fetal growth restriction (FGR) is still unknown. Here, we show that the human FGR fetus has a strikingly reduced umbilical uptake of both oxygen and glucose. In 30 healthy term and 32 FGR human pregnancies, umbilical volume flow (Qumb) and parallel umbilical vein (uv) and artery (ua) blood samples were obtained at elective Cesarean section to calculate fetal glucose and oxygen uptake as Qumb · Δ (uv−ua) differences. Umbilical blood flow was significantly lower in FGR pregnancy (−63%; P <0.001) but not when normalized for fetal body weight. FGR pregnancy had significantly lower umbilical oxygen delivery and uptake, both as absolute values (delivery: −78%; uptake: −78%) and normalized (delivery: −50%; uptake: −48%) for fetal body weight (all P <0.001). Umbilical glucose absolute delivery and uptake were significantly reduced (delivery: −68%; uptake: −72%) but only glucose uptake was decreased when normalized for fetal body weight (−30%; P <0.05). The glucose/oxygen quotient was significantly increased (+100%; P <0.05) while glucose clearance was significantly decreased (71%; P <0.001) in FGR pregnancy (both P <0.05). The human fetus in FGR pregnancy triggers compensatory mechanisms to reduce its metabolic rate, matching the proportion of substrate consumption relative to oxygen delivery as a survival strategy during complicated pregnancy. Abstract : Supplemental Digital Content is available in the text.